Biomolecular Assemblies Combining Two Orthogonal Copper‐Mediated Ligations in a One‐Pot Reaction. Issue 16 (20th March 2015) - Grassin, Adrien; Claron, Michaël; Boturyn, Didier
Abstract The access to multifunctional biomolecular compounds involves multistep reactions usually with a complicated protection scheme and lengthy separation processes. The development of a strategy combining several orthogonal ligations is highly desirable. Herein, we introduce a new method that involves two orthogonal copper‐mediated ligations of azide with alkyne, and amine with thioacid. We established compatible conditions to carry out molecular assemblies of three different chemical components in a single one‐pot reaction. The effectiveness of the method was demonstrated in the synthesis of biomolecular compounds that are known to target tumor tissue. The simple reaction conditions suggest that this strategy of combining several orthogonal ligations could have wide potential for the chemical synthesis of complex macromolecules.